New species and new records of ground spiders (Araneae: Gnaphosidae) from Cyprus - Chatzaki, Maria; Russell-Smith, Anthony (Zootaxa, 2017)
New taxonomic data on the ground spiders of the family Gnaphosidae from the island of Cyprus are presented. Three species are proposed as new to science (Drassyllus cyprius sp. n., Setaphis mccowani sp. n., Zelotes limnatis sp. n.). The male of Synaphosus shirin Ovtsharenko, Levy & Platnick, 1994 and the female of Zelotes zekharya Levy, 2009 are described for the first time. The transfer of Zelotes helvolus (O.P. Cambridge, 1872) and Z. helvoloides Levy, 1998 (the latter not recorded in Cyprus) to Cryptodrassus is proposed. The mismatching of male and female of C. helvoloides is discussed, and the female originally described as C. helvoloides is transferred to C. helvolus. Micaria pallipes (Lucas, 1846) is here recorded and the synonymy with Castanilla marchesii Caporiacco, 1936 is rejected, while the paralectotype of Castanilla marchesii is here assigned to Leptodrassex algericus Dalmas, 1919. Finally a male Poecilochroa still not attributed to a known or new species is described.